Analysis strategy for multi-criteria optimization: Application to inter-seasonal solar heat storage for residential building needs. (15th March 2019) - Launay, S.; Kadoch, B.; Le Métayer, O.; Parrado, C.
Abstract: As energetic systems become more and more complex, it is necessary to develop strategies for analyzing the influence of the parameters as well as their couplings. This approach is even unavoidable when the optimization procedure is based on multi-criteria. In the present work, we propose an analysis strategy for multi-criteria optimization applied to inter-seasonal solar heat storage for residential building energy needs, including heating and domestic hot water. The modeling is based on simplified equations of the components, while keeping the main physical and coupling phenomena. A sensitivity study is applied to the corresponding energetic system in order to identify the most relevant parameters and couplings interacting on the various output objectives. Several simulations are performed to investigate a multi-objective optimization and various figure representations are presented to refine the analysis. Highlights: Dynamical system study including inter-seasonal and short-term energy storages. System analysis to insure heating and domestic hot water demands. Achievement of sensitivity analysis for parameters and coupling parameters. Investigation of weighted multi-criteria optimization. Implementation of combined analysis to promote a general efficient methodology.